Outcome of patients with localized orbital sarcoma who relapsed following treatment on Intergroup Rhabdomyosarcoma Study Group (IRSG) Protocols‐III and ‐IV, 1984–1997: A report from the Children's Oncology Group123. Issue 3 (7th September 2012) - Raney, Beverly; Huh, Winston; Hawkins, Douglas; Hayes‐Jordan, Andrea; Million, Lynn; Rodeberg, David; Teot, Lisa; Anderson, James; ,
Abstract Background We wanted to ascertain patterns of recurrence, re‐treatment, and outcome among 188 eligible patients treated for localized orbital sarcoma on IRSG Protocols III/IV, 1984–1997. Procedure Retrospective chart review. Results Twenty‐four of 188 patients (12.8%) developed local (n = 22) or distant relapse (n = 2) at 0.057–7.05 years (median, 1.58) after enrollment. Ages at study entry were 0.14–17 years (median, 5 years). Initial tumor operations included biopsy (n = 20) or gross resection with microscopic residual (n = 4). Initial tumor diameters were 0.5–7 cm (median, 3). Pathologic subtypes were embryonal rhabdomyosarcoma (ERMS, n = 19), sarcoma not otherwise specified (n = 2), and alveolar RMS, botryoid ERMS, or undifferentiated sarcoma (n = 1 each). Initial treatment included vincristine/dactinomycin (n = 24) including an alkylator (n = 4) and radiotherapy (RT, n = 21). Twenty patients responded, 14 completely, 6 partially. After recurrence, patients underwent orbital exenteration (n = 10), enucleation (2), tumor excision (3), or biopsy (1); 7 had no operation, and 1 had no data. Post‐relapse chemotherapy included combinations of etoposide (n = 14 patients), doxorubicin (14), ifosfamide (12), cyclophosphamide (7), and dacarbazine (n = 1). Six patients received RT, including four previously treated and two not irradiated initially. Two patients died; one at 1.79 years after contralateral brain metastasis followed by local recurrence, and another at 2.49 years after multiple local recurrences. Twenty‐two patients (91.7%) survived sarcoma‐free for 0.04–17 years (median, 6.9) after relapse, and 18 of 22 (82%) were alive ≥5 years after relapse. Conclusion Survival following recurrent localized orbital sarcoma appears likely after vigorous re‐treatment given with curative intent. Pediatr Blood Cancer 2013; 60: 371–376. © 2012 Wiley Periodicals, Inc.